(untitled) (Salam International Academic Journal, 2020)
Despite the perceived impact of Small and Medium Enterprises on the growth and development of an economy as observed in the literature, and also the government effort at promoting SMEs in the country, the impact of SMEs to Gross Domestic Product in Afghanistan is reported to be low, thus affecting every other aspect of the economy. As the GDP grows, it is expected that it tickles down to other sectors of the economy by ways of greater utilization of local raw materials, employment generation, encouragement of rural development, development of entrepreneurship, mobilization of local savings, linkages with bigger industries, provision of regional balance by spreading investments more evenly, provision of avenue for self-employment and provision of opportunity for training managers and semi-skilled workers. Unfortunately, the reverse is the case. It is against this back drop that this study examines the effect of small and medium enterprises on economic growth in Nigeria by modeling the effect of SMEs, government expenditure in promoting SMEs, Employment generation growth rate and level of Corruption, commercial bank credits and lending rate to SMEs on economic growth in Nigeria using an econometric regression model of the Ordinary Least Square (OLS). From analysis of the study, it is observed that small and medium enterprise, government expenditure to small and medium enterprise, employment generations, commercial bank credit to small and medium enterprise and lending rate to small and medium enterprises have a positive impact on economic growth in Afghanistan. Corruption has a negative impact on economic growth in Afghanistan. However, all the explanatory variables have significant impacts on economic growth in Afghanistan. Based on the above findings, the study recommends that the government should as a deliberate policy, encourage rural based industrialization whereby investors in different communities should be encourage to establish small and medium scale industries that would be based entirely on local raw materials, including machines and equipment. Government monetary policies should also be designed to favor the SMEs in terms of lending rate, interest rate and exchange rate. Arguably, this will help to boost the economy and create more employment.